2023
DOI: 10.1051/0004-6361/202245657
|View full text |Cite
|
Sign up to set email alerts
|

GRB minimum variability timescale with Insight-HXMT and Swift

Abstract: Context. There has been significant technological and scientific progress in our ability to detect, monitor and model the physics of gamma-ray bursts (GRBs) over the 50 years since their first discovery. However, the dissipation process thought to be responsible for their defining prompt emission is still unknown. Recent efforts have focused on investigating how the ultrarelativistic jet of the GRB propagates through the progenitor's stellar envelope, for different initial composition shapes, jet structures, m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 127 publications
1
11
0
Order By: Relevance
“…Such a (dominant) subkilohertz QPO frequency has not been inferred from GRB910711. Further evidence for the origin of subkilohertz variability may also come from population statistics (Camisasca et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Such a (dominant) subkilohertz QPO frequency has not been inferred from GRB910711. Further evidence for the origin of subkilohertz variability may also come from population statistics (Camisasca et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Golkhou & Butler (2014); Golkhou et al (2015) defined the MVT as the transition between correlated and uncorrelated variability, which is approximately the same as the rise time of the shortest pulse in a light curve. Recently, Camisasca et al (2023) defined MVT as the FWHM duration of the shortest pulse in the time domain and reported a very strong correlation between their results and those of Golkhou & Butler (2014), but they are not completely consistent; in particular, some differ by more than a decade. In addition, some authors found that half of the shortest Bayesian block (BB) is consistent with the MVT obtained by the wavelet analysis of individual GRBs (e.g., Ackermann et al 2014;Vianello et al 2018), but to our knowledge, the MVT estimated by BB has not been systematically compared with the results by other methods to prove its robustness, which will be demonstrated in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The GRB prompt-emission light curves are of paramount importance in understanding the characteristics of the central engine. The T 90 duration describes the timescale over which the central engine is active, and the minimum variability timescale (t mvts ) gives an idea about the compactness of the emitting region (Sari & Piran 1997;Golkhou et al 2015;Sonbas et al 2015; see also Camisasca et al 2023 for a recent work that studied the correlation of t mvts of GRBs with quantities such as peak luminosity and Lorentz factor). We, therefore, explored the effect of these two parameters on the clusters of KNassociated GRBs.…”
Section: Inference Of the Physical Parameters Of The Clusters Of Kn-a...mentioning
confidence: 99%